Detection of Coronary Artery Disease by an Erectile Dysfunction Questionnaire - Mehrab Sayadi; Reza Elmafshar; Iman Razeghian-Jahromi; Mohammad Javad Zibaeenezhad (Cardiology Research and Practice)
Background. Erectile dysfunction (ED) has been become an important health challenge in recent years affecting the quality of life significantly. In addition to imposed social problems, it may warn the existence of cardiovascular diseases especially that of ischemic heart disease (IHD). We aimed to investigate the association between ED and coronary artery disease (CAD) in a population of patients with stable angina based on angiographic findings. Methods. In this cross-sectional study, among patients who are diagnosed with stable angina referring for coronary angiography (excluding those with acute coronary syndrome), 200 patients were selected. They were divided equally into two groups of case and control. The former were positively CAD patients and the latter were normal peers, with respect to angiographic results. International index of erectile function (IIEF) questionnaire was used in order to evaluate erectile function during recent four weeks. Statistical analyses of the t-test and logistic regression were performed. The significance level was considered as a P value less than 5%. Results. The age range of the patients was 40–65 years old. The case group was significantly older (P=0.001). There was a remarkable relation between the low score from IIEF (ED) and existence of CAD. Also, the severity of ED was in a close relationship with severity of CAD. In addition, dyslipidemia in terms of high LDL and low HDL was associated with both ED and severity of CAD. Conclusion. Other than CAD, ED could be considered as one of the manifestations of atherosclerosis. Accordingly, the IIEF questionnaire is a useful tool to early diagnosis of CAD. Also, IIEF-derived scores estimate CAD severity. We suggest subjects with low score of IIEF examine their cardiovascular health with special attention to possible existence of IHD.